2007
DOI: 10.1159/000107382
|View full text |Cite
|
Sign up to set email alerts
|

Cryptogenic Stroke, Aortic Arch Atheroma and Patent Foramen Ovale

Abstract: Cryptogenic stroke represents a diagnostic challenge. Several conditions have been found to be more frequent in patients with cryptogenic stroke. Aortic arch atheroma (AAA) and patent foramen ovale (PFO) have been shown to be highly prevalent in the adult population, especially in patients with ischemic cerebrovascular events, particularly cryptogenic strokes. In both conditions, clinical relevance and stroke risk are related to age, with AAA being more frequent and severer in patients >55 years, and the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Established risk factors for stroke, such as previous stroke or transient ischemic attack (TIA), atrial septal aneurysm, aortic arch atheroma, atrial fibrillation, and left atrial dilation, were included along with other comorbidities as potential confounders in propensity analyses. 14,[23][24][25][26][27][28][29][30][31][32][33]…”
Section: Outcome Measures and Risk Factorsmentioning
confidence: 99%
“…Established risk factors for stroke, such as previous stroke or transient ischemic attack (TIA), atrial septal aneurysm, aortic arch atheroma, atrial fibrillation, and left atrial dilation, were included along with other comorbidities as potential confounders in propensity analyses. 14,[23][24][25][26][27][28][29][30][31][32][33]…”
Section: Outcome Measures and Risk Factorsmentioning
confidence: 99%
“…Some studies have evaluated the presence of significant atheromatosis of the aortic arch in patients with cryptogenic stroke, but the association between aortic arch atheroma and cryptogenic stroke has been limited to patients Ͼ60 years old. 1,2 In fact, the role of atherosclerosis in young adults with cryptogenic stroke has been mostly limited to the evaluation of the prevalence of cardiovascular risk factors in these patients. [3][4][5] Also, a role for patent foramen ovale (PFO) in the pathogenesis of cryptogenic stroke in patients Յ55 years old has been suggested on the basis of case-control studies that have shown a higher prevalence of PFO among these patients compared with stroke-free control subjects, 6 but no studies have determined whether or not the atherosclerotic burden in young patients with cryptogenic stroke might vary depending on the presence of a PFO.…”
mentioning
confidence: 99%
“…Of TEE-identified aortic arch lesions showing an association with LSCA plaque, large arch plaque (≥4.0 mm) and ulcer are typical findings of advanced atherosclerosis and indicators for stroke and systemic atherosclerotic disease [1,2,3,4,5,6,7,8,20,21,22,23,24,25]. A spontaneous echo contrast is a pulsatile, swirling echo pattern that is associated with the rouleau phenomenon due to erythrocyte aggregation, increased plasma fibrinogen levels, and plasma viscosity.…”
Section: Discussionmentioning
confidence: 99%